1997
DOI: 10.1002/(sici)1099-1573(199709)11:6<441::aid-ptr126>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Screening of 17 Guatemalan medicinal plants for platelet antiaggregant activity

Abstract: The platelet antiaggregant activity of 17 aqueous extracts of plants traditionally used in Guatemala for the treatment of ‘blood disorders’ and parasitic infections were assayed. The aggregation of washed human platelets induced by thrombin (0.075 U/mL) was inhibited by extracts of Tridax procumbens, Tagetes lucida, Annona reticulata, Neurolaena lobata, Bixa orellana, Rauvolfia tetraphylla, Petiveria alliacea and Tecoma stans. The other extracts did not have clear inhibitory effects, and indeed caused some pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 11 publications
0
26
0
1
Order By: Relevance
“…The plant extract mixed with castor oil is prescribed for refractory ailments and bark decoction is used for chronic refractory skin diseases and destroys parasites [4]. The root is used to stimulate uterine contractions and is recommended for use in difficult childbirth cases [5].…”
Section: Introductionmentioning
confidence: 99%
“…The plant extract mixed with castor oil is prescribed for refractory ailments and bark decoction is used for chronic refractory skin diseases and destroys parasites [4]. The root is used to stimulate uterine contractions and is recommended for use in difficult childbirth cases [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous pharmacological studies have revealed that Bixa orellana extracts possess antiprotozoal, anthelmintic and platelet antiaggregant activity (Villar et al, 1997;Barrio et al, 2004). Root extracts have been reported to have spasmolytic activity (Mans et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…orellana L. extracts have antiprotozoal, anthelmintic, platelet antiaggregant, [14,15] and anticlastogenic activity. [16] The root extracts have spasmolytic activity, whereas leaf and branch extracts were effective at neutralizing the effects of snake venoms.…”
Section: Discussionmentioning
confidence: 99%